Pengembangan E-LKPD Berbasis Poblem Based Learning (PBL) Terintegrasi Berpikir Kritis Pada Materi Sistem Ekskresi Manusia Kelas XI SMA - Gultom, Putri Rohani; Wan Syafi’i; Darmadi (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2025)
This study aims to develop an Electronic Student Worksheet (E-LKPD) based on Problem-Based Learning (PBL) integrated with critical thinking skills on the topic of the human excretory system for Grade XI senior high school students. The research employed a Research and Development (R&D) approach by adapting the ADDIE model (Analyze, Design, Development, Implementation, and Evaluation). This study was conducted up to the development stage. The trial subjects included two expert validators, 10 biology education students, two biology teachers, and 30 Grade XI students from SMAN 2 Pekanbaru. The instruments used consisted of a validation sheet, student response questionnaire (students and prospective teachers), and teacher response questionnaire. The validation results showed that the E-LKPD was categorized as "very valid", with an average score of 3.51. The first limited trial (with university students) indicated that the E-LKPD was "very good", with an average score of 3.59. The second limited trial (with teachers and students) yielded average scores of 3.80 and 3.79, respectively, indicating "very good" responses. The practicality test resulted in an average score of 3.72, categorized as "very good/practical", while the overall quality assessment yielded a score of 3.61, also classified as "very good". The development of this E-LKPD demonstrates that the integration of the PBL model with critical thinking indicators effectively facilitates students in identifying problems, analyzing information, and constructing solutions based on the concept of the human excretory system. Therefore, the developed E-LKPD is deemed suitable for use as a supplementary teaching material in biology learning that emphasizes the enhancement of critical thinking skills.